(3GdWGbI aj GdNdjL (B:s - (3JMOjGJ h JgOjOGJs; (3eQcR GdEeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjIs; (3eDJeQ GdWGbI GdSfhj (B((3Gd (B1 : 14-15 (3JTQjf Ghd (B1995 : (3GHh XHj (B)s; (3MeGO , Ndjds ((3GHh XHjs (3eQcR GdEeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjIs, 2014)
(3jHOC GdcJGH HdeMI JGQjNjI Yf OhQ efWbI GdNdjL aj GShGb GdWGbI GdYGdejI (B/ (3jSJYQV GSHGH GfNaGV GSYGQ GdfaW(B/(3LOhd GYeGd GdeNWWGJ GdGSJQGJjLjI GdeJYdbI HGdWGbI aj Ohd GhHc(B/(3jYQV GdNjGQGJ GdeJGMI aj Shb GdWGbI Ydi GdeOi GdbQjH(B/ (3jYQV GdYbHGJ GdJj JhGLg Ohd eLdS GdJYGhf dOhd GdNdjL GdYQHjI (B/ (3jNdU Gdi VQhQI JfhjY eUGOQ GdONd aj efWbI GdNdjL hGdHMK Yf eUGOQ HOjdIs
(3GdcJGH KeQI ef KeGQ eDJeQ GdWGbI GdSfhj GdGhd GdPj fXeg GdeQcR jhej (B14 (3h (B15 (3JTQjf GdGhd(B1995 (3aj GHh XHjs
Keywords: (3GdHJQhd (B-- (3GdLhGfH GdSjGSjIs; (3GdHJQhd (B-- (3GdNdjL GdYQHj (B-- (3LhGfH GdSjGSjIs